In vitro Cytotoxicity Comparison of MTA Fillapex, AH-26 and Apatite Root Canal Sealer at Different Setting Times - Jafari, Farnaz; Aghazadeh, Marzieh; Jafari, Sanaz; Khaki, Faraz; Kabiri, Fahimeh (Iranian Endodontic Journal, 2017)
Introduction: This study aimed to compare the cytotoxicity of MTA Fillapex, AH-26 and Apatite root canal sealers at different times after mixing. Methods and Materials: In this in vitro study, MTA Fillapex, AH-26 and Apatite root canal sealer were spilled uniformly by 40 µm mesh in a 96-well plate. Then, human fetal foreskin fibroblast cell line (HFFF2) were added to each sealer cell culture medium. Cytotoxicity was measured using MTT assay after 24, 48 and 72 h and seven days. Multiple comparisons were done using analysis of variances (ANOVA) and Scheffe’s post hoc test. Results: All studied sealers exhibited severe cytotoxicity (more than 70%) except for Apatite sealer (95%) at 48 h after mixing. Cytotoxicity of MTA Fillapex and AH-26 were similar (P>0.05) at 24, 48 and 72 h and 7 days after mixing of sealers. Cytotoxicity of MTA Fillapex and Apatite root canal sealer, at 24 and 48 h, were significantly different (P=0.003 and P=0.000, respectively); MTA Fillapex was more cytotoxic. However in 72 h and 7 days after mixing, the difference was not significant (P>0.05). At 24 and 48 h after mixing, AH-26 was more cytotoxic (P=0.002 and P=0.000, respectively). Same as above at 72 h and 7 days after mixing, their cytotoxicity were similar (P>0.05). Conclusion: Overall cytotoxicity of all studied materials were severe. However, it was observed that the cytotoxicity of MTA Fillapex, AH-26 and Apatite root canal sealer decreased over time. Apatite root canal sealer exhibited the least cytotoxicity. Cytotoxicity of MTA Fillapex and AH-26 were similar at different time intervals. Keywords: Cytotoxicity; MTT Assay; Root Canal Sealer